(untitled) (Eurasian Medical Research Periodical, 2024)
Within 1 year after insertion of the IUD (group 1), the duration of menstruation in those examined significantly increased, pain and scanty discharge appeared, and the volume of menstruation, which was absent before insertion of the IUD, increased. The problem of contraception, which provides effective birth control in recent decades, remains one of the most pressing in gynecology